Trade Intensity and Business Cycle Synchronicity in Africa - (:unkn) unknown (My University, 2009)
Business cycle synchronicity, which is the key requirement for sharing a common currency, is not particularly strong within the prospective African monetary unions. However, this parameter is not irrevocably fixed and may be endogeneous vis-à-vis the integration process. For example, trade may increase the similarity of economic disturbances. This paper tests such an effect among the 53 African countries from 1965 to 2004. The estimated results suggest that trade intensity increases the synchronisation of business cycles in the African context. The magnitude of the ‘endogeneity effect' is, however, smaller than similar estimates among industrial countries.
Keywords: African Research